Long-term quality assurance of [(18)F]-fluorodeoxyglucose (FDG) manufacturing - Gaspar, Ludovit; Reich, Michal; Kassai, Zoltan; Macasek, Fedor; Rodrigo, Luis; Kruzliak, Peter; Kovac, Peter (American journal of nuclear medicine and molecular imaging, 2016)
Nine years of experience with 2286 commercial synthesis allowed us to deliver comprehensive information on the quality of (18)F-FDG production. Semi-automated FDG production line using Cyclone 18/9 machine (IBA Belgium), TRACERLab MXFDG synthesiser (GE Health, USA) using alkalic hydrolysis, grade "A" isolator with dispensing robotic unit (Tema Sinergie, Italy), and automatic control system under GAMP5 (minus2, Slovakia) was assessed by TQM tools as highly reliable aseptic production line, fully compliant with Good Manufacturing Practice and just-in-time delivery of FDG radiopharmaceutical. Fluoride-18 is received in steady yield and of very high radioactive purity. Synthesis yields exhibited high variance connected probably with quality of disposable cassettes and chemicals sets. Most performance non-conformities within the manufacturing cycle occur at mechanical nodes of dispensing unit. The long-term monitoring of 2286 commercial synthesis indicated high reliability of automatic synthesizers. Shewhart chart and ANOVA analysis showed that minor non-compliances occurred were mostly caused by the declinations of less experienced staff from standard operation procedures, and also by quality of automatic cassettes. Only 15 syntheses were found unfinished and in 4 cases the product was out-of-specification of European Pharmacopoeia. Most vulnerable step of manufacturing was dispensing and filling in grade "A" isolator. Its cleanliness and sterility was fully controlled under the investigated period by applying hydrogen peroxide vapours (VHP). Our experience with quality assurance in the production of [(18)F]-fluorodeoxyglucose (FDG) at production facility of BIONT based on TRACERlab MXFDG production module can be used for bench-marking of the emerging manufacturing and automated manufacturing systems.